2018
DOI: 10.1101/424762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metatranscriptomic and thermodynamic insights into medium-chain fatty acid production using an anaerobic microbiome

Abstract: Importance 46Mixed communities of microbes play important roles in health, the environment, 47 agriculture, and biotechnology. While tapping the combined activity of organisms within 48 microbiomes may have advantages over the use of pure cultures for biomanufacturing, 49 harnessing the metabolism of these mixed cultures remains a major challenge. Here, we 50 predict metabolic functions of bacteria in a microbiome that produces medium-chain fatty 51 acids from a renewable feedstock. Our approach and findings c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…These observed results were consistent with the metabolic traits of butyrate-producing bacteria for butyrate production, which are normally identified in gut microbiome in healthy adults [32]. Moreover, we also found that Roseburia exhibited a high number of genes involved in xylulose-5-phosphate/fructose-6-phosphate phosphoketolase (Xfp, ECs: 4.1.2.9 and 4.1.2.22), which is the key catalytic enzyme in the hemicellulosic complex oligosaccharides fermentation pathway [34]. This finding is consistent with the most recent genome-scale metabolic reconstruction of the carbohydrate degradation and utilization pathways of Roseburia, which demonstrated the ability of Roseburia species to ferment pentoses (e.g., xylose and arabinose) and oligosaccharides (e.g., xylooligosaccharides, arabinoxylans and arabinogalactans) as carbon sources for growth through Xfp [35].…”
Section: Bacterial Community-wide Metabolic Functional Analysis Involsupporting
confidence: 83%
“…These observed results were consistent with the metabolic traits of butyrate-producing bacteria for butyrate production, which are normally identified in gut microbiome in healthy adults [32]. Moreover, we also found that Roseburia exhibited a high number of genes involved in xylulose-5-phosphate/fructose-6-phosphate phosphoketolase (Xfp, ECs: 4.1.2.9 and 4.1.2.22), which is the key catalytic enzyme in the hemicellulosic complex oligosaccharides fermentation pathway [34]. This finding is consistent with the most recent genome-scale metabolic reconstruction of the carbohydrate degradation and utilization pathways of Roseburia, which demonstrated the ability of Roseburia species to ferment pentoses (e.g., xylose and arabinose) and oligosaccharides (e.g., xylooligosaccharides, arabinoxylans and arabinogalactans) as carbon sources for growth through Xfp [35].…”
Section: Bacterial Community-wide Metabolic Functional Analysis Involsupporting
confidence: 83%
“…Relative transcript abundances as a proxy for expression levels were calculated from the total filtered mRNA reads from 56 RNA samples, which were individually mapped against the recovered MAGs, normalized for respective genome length and sequencing depth and expressed as transcripts per million (TPM) (Supplementary Table 2 ) 19 , 43 . The two most abundant anammox MAGs (~18% relative abundance) together were significantly ( p < 0.05, Student’s t -test) responsible for the highest transcriptional activity during the 20 °C and 14 °C regimes, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Beside substrate uptake kinetics, SBRs can be used for the fundamental understanding and mathematical description of the effect of product toxicity and changing ethanol-to-acetate ratios on chain elongating organisms in dynamic environments. Omics techniques in combination with metabolic modeling could be used to identify labor division in microbial communities fed with a complex substrate and gain a deeper understanding of the effect of environmental conditions on the metabolic flux though microbial communities ( Scarborough et al, 2018 ). Lastly, integrated reactor setups can be exploited for testing the industrial potential of different cultivation strategies.…”
Section: Discussionmentioning
confidence: 99%